Periprosthetic fractures in total hip arthroplasty: an epidemiologic study - Sarvilinna, Roope (Springer-Verlag, 2003)
This study was based on data from the Finnish Arthroplasty Register. From 1990 to 1999, 33,154 primary hip arthroplasties were performed in Finland. Only periprosthetic fractures treated by a revision arthroplasty were registered. The six most used femoral components were compared using survival analysis and Cox's regression model. The incidence of periprosthetic fractures was calculated separately for the years 1990–1994 and 1995–1999. The incidence in the first period was greater than in the latter. Survival analysis and Cox's regression model showed that gender, prosthesis type and age were of no significance as risk factors for periprosthetic fractures.